Environmental characterization and metagenomics analysis of biotic and abiotic factors in North Selangor Peat Swamp Forest, Malaysia - Hamidu, Saadu (2020)
The North Selangor Peat Swamp Forest (NSPSF), like all other peatland ecosystems are subjected to various of threats such as forest fire, wild animal poaching, expansion of area for agricultural and industrial activity, canal construction, deforestation, and air, water and land pollutions. Moreover, limited fundamental studies have been conducted in this unique ecosystem, especially in the aspect of microbial ecology that associated with the continuous anthropogenic activities of the protected forest. In general, this study determines the environmental characterization and metagenomics analysis of biotic and abiotic factors in North Selangor Peat Swamp Forest, Selangor, Malaysia. Firstly, this study determines the current environmental variables of undisturbed and disturbed areas. Secondly, the composition and diversity of bacterial communities in the fish gut contents, water and soil of undisturbed and disturbed areas were identified. Thirdly, the taxa and functional genes biomarkers of bacteria in soil samples of undisturbed and disturbed areas were determined. Lastly, this study identified the relationships between the environmental variables and bacterial taxa biomarker from soil of undisturbed and disturbed areas. In order to understand the impacts of natural and human induced factors on the bacterial communities in NSPSF, two areas namely NSPSF (undisturbed) and its nearby (disturbed) areas were selected in this study. In each area, three sites were selected, namely Sungai Karang Peat Swamp Forest site 1 (SKPSF-1), Raja Musa Peat Swamp Forest (RMPSF) and Sungai Karang Peat Swamp Forest site 2 (SKPSF-2) for undisturbed area, while for disturbed area, paddy field (PF), forest fire (FF) and oil palm plantation (OP) areas were selected. The environmental variables of anthropogenic activities, forest characteristics and water physico-chemical parameters in undisturbed and disturbed areas were determined. Following that, the metagenomics techniques was utilized to assess the composition, diversity, taxonomical biomarkers and functional genes of bacteria in the undisturbed (U) and disturbed (D) samples offish gut contents (UF and DF), water (UW and DW) and soil (US and DS) in the study areas, as well as to relate these metagenomics findings with the measured environmental variables. The findings on anthropogenic activities revealed that the disturbed areas have higher scores in water (WP), land (LP) and noise (NP) pollutions and agricultural activity (AA). Other anthropogenic activities that recorded in disturbed areas were distance from human settlement (DHS), state of accessibility (SA), and deforestation (DL), and these were the predominant anthropogenic activities in disturbed area. Whereas, construction activities (CR) cut across all the sites. The higher seedling percentage (PS) in OP was observed and conversely, the percentage of trees (PT) and number of falling trees (FT) appeared to be correspondingly higher in SKPSF-1. The PF in the disturbed area was characterized by high relative light intensity (RLI). Conversely, RLI was relatively lower in the undisturbed area. The undisturbed area indicates lower dissolved oxygen (DO) values and notably increases from undisturbed to disturbed areas, particularly in PF and OP. The FF was an exception, which was observed to have comparatively lower DO concentration. Some of anthropogenic activities such as DHS, SA, DL and AA correlated closely with NH3-N and Fe in the disturbed area, while sign of fire (SF) in the undisturbed area was associated with NOf. The metagenomics analyses in undisturbed and disturbed areas revealed a rich and diverse bacterial community across the 18 samples of fish gut contents, water and soil. Moreover, the alpha indexes showed significant difference (p < 0.05) between the disturbed and undisturbed sites of each sample. The rarefaction among the samples showed curves, at points where the number individual organisms increase, but the number of species remain constant in the study area. The Proteobacteria appeared to be the most dominated phyla, followed by unassigned taxa, Firmicutes and Actinobacteria, and they were relatively significance in disturbed area of DF and DS samples. The finding showed significant differences in relative abundance of some phyla between undisturbed and disturbed areas. The higher relative abundance of some taxa such as Novosphingobium in UW and Desulfobacter in DS indicates the presence of pollutants in undisturbed and disturbed areas. Similarly, phylum Acidobacteria was apparently present throughout the undisturbed samples and was the most common bacterial group detected in undisturbed area. Furthermore, among the three samples (soil, water and fish gut content), the soil samples recorded higher difference between the OTUs in undisturbed and disturbed areas. Hence, differential features of bacterial community in the soil were predicted. The metagenomics taxonomic features of soil samples showed ACK_Ml, Hydrogenophilaceae and Thiobacillus were taxa biomarker that prevalent in undisturbed samples, whereas, the taxa biomarker identified in disturbed area were p_WPS_2, Planctomycetaia and Gemmatales. The discriminatory metagenomics features detected KO biomarkers through LEfSe which were notably higher in DS samples, and most of them were associated with chemotaxis and related electron transfer. Whereas, majority of the KO biomarkers in US samples were linked with transport, adhesion of proteins and iron. The functional biomarkers detected in DS samples were connected to synthesis of proteins and amino acid related enzymes such as DNA replication, translation factors, RNA polymerase and aminoacyl_tRNAbiosynthesis were observed. In contrast, most of the functional biomarkers depicted in US samples related to metabolism and degradation of chemicals like ascorbate and alderate metabolism, CS_branched dibasic acid metabolism, biosynthesis and biodegradation of secondary metabolites, and dioxin degradation. Metagenome contribution by gene family in soil samples revealed Enterobacteriaceae and Aeromonadaceae, to be associated with K03088. However, only Moraxellaceae was predicted in DS sample which was linked to K03406. The higher number of taxa biomarker and metagenomic contribution by genes family were predicted in the DS samples. Thus, it suggests the presence of consortium of bacteria with synergistic or antagonistic actions of bacteria in the disturbed area, and this could have been the source of ecological difference between disturbed and undisturbed area ofNSPSF. Redundancy analysis was used to analyse and summarise the relationships between the anthropogenic activities, forest characteristics and water physico-chemical factors with bacterial taxa biomarker of soil samples in undisturbed and disturbed areas. The taxa biomarker connected to five anthropogenic activities of SA, AA, CR, DL and DHS including c_TKl 7, Legionella, p_WPS_2, Spirochaeta and Acinetobacter in DS samples. Interestingly, similar taxa biomarker particularly C_TKl7, g_Legionella, p_WPS_2, g_Spirochaeta and g_Acinetobacter as obtained in anthropogenic factors were also were strongly linked to the two forest characteristics of RLI and PS that found in DS samples. Whereas, the members of Hydrogenophilaceae, Thiobacillus, Candidatus Rhodoluna and f_ACK_Ml and Methylococcales were the biomarkers that more localized in US samples with closer association to NOf, turbidity and water depth. In this study, some recommendations were proposed such as to regulate indiscriminate construction of canals, roads, and other buildings in the both undisturbed and disturbed areas. As such, environmental impact assessment should be carried out and this recommendation should be adhered prior to any project in and around NSPSF. On the forest characteristics, the seedlings could be complemented through artificial nurseries in undisturbed areas which recorded low PS. Despite the differences in environmental factors between disturbed and undisturbed areas, no significant difference obtained between the two areas in term of the bacterial diversity and composition. Interestingly, NOf, turbidity and water depth have strong associations with taxa biomarker in undisturbed area. Thus, suggesting that change in these three factors could likely affect the distribution and abundance of species within the bacterial biomarker identified in NSPSF. Indeed, further study on metagenomics analysis of biotic and abiotic factors could be carried out to exploit the effects of seasonal variation on environmental conditions of NSPSF. Additionally, the unclassified taxa of bacterial community in NSPSF could also be investigated to bring out its taxonomical and functional features. This study could potentially provide guidelines for effective identification, remediation and restoration of degraded peat swamp forest, as well as give the insight in ecological monitoring and conservation of NSPSF and its environment.